MANAGEMENT ENSURE FAVORABLE CONDITIONS FORINNOVATION ORGANIZATIONS - G. Matveev (Вестник университета, 2016)
Focusing on innovative development of the economy determines the high urgency of solving the problem of creating appropriate conditions for economic entities. It is obvious that the need to create them, first of all, a fairly complete and objective picture of the real situation of the organization, the state of the external and internal environment. Such knowledge management organization can receive based on the characteristic set of relevant indicators that reflect not only the absolute evaluation of individual components of the external and internal environment, but they are interconnected and interdependent. The article summarizes the results of studies on the establishment of these indicators and formulate the conceptual provisions for their use in the management of the creation of conditions for the innovation activities of the organization, through the mechanism of economic security .